Economic Welfare and Inequality in Iran Developments since the Revolution - Farzanegan, Mohammad Reza.; Alaedini, Pooya; SpringerLink (Online service) (New York : Palgrave Macmillan US (Imprint), 2016)
This book examines economic inequality and social disparity in Iran, together with their drivers, over the past four decades. During this period, income distribution and economic welfare were affected by the 1979 Revolution, the eight-year war with Iraq, post-war privatization and economic liberalization initiatives carried out under the Rafsanjani and Khatami administrations, the ascendance of a populist economic platform under the Ahmadinejad administration, and the lifting of energy and financial sanctions under the Rouhani administration. Featuring a mix of scholars, including Iranian academics who experienced these changes and are publishing in English for the first time, this collection offers quantitative and descriptive studies of the country's post-revolutionary economic development and disparities. In most chapters, a hypothesis is developed from existing theories or observations, which is then tested using available data. This unique combination of new voices, academic as well as personal experiences, and scientific methods will be a valuable addition to the library of the scholars of modern Iran's economy and society.
1. Iran's Post-revolutionary Social Justice Agenda and Its Outcomes: Evolution and Determinants of Income Distribution and Middle-Class Size -- 2. Poverty, Inequality, and Income Mobility in Iran: A Pseudo-Panel Approach -- 3. Oil rents, Political Institutions, and Income Inequality in Iran -- 4. Housing Costs and Inequality in Post-Revolutionary Iran -- 5. Gender Inequality and Income Inequality in Iran -- 6. Aging and Gender Inequality in Contemporary Iran -- 7. Effect of Oil Sanctions on Household Welfare in Iran: New Evidence from a CGE Model -- 8. Household Welfare in Iran under Banking Sanctions: From Open Economy toward Autarchy.
Keywords: Economic history; Development economics; International Economics; Economy-wide Country Studies